Structure and Biological Properties of Surface-Engineered Carbon Nanofibers. (9th May 2019) - Smolka, Wojciech; Panek, Agnieszka; Gubernat, Maciej; Szczypta-Fraczek, Aneta; Jelen, Piotr; Paluszkiewicz, Czeslawa; Markowski, Jaroslaw; Blazewicz, Marta
Abstract : The aim of this work was to manufacture, using the electrospinning technique, polyacrylonitrile- (PAN-) based carbon nanofibers in the form of mats for biomedical applications. Carbon nanofibers obtained by carbonization of the PAN nanofibers to 1000°C (electrospun carbon nanofibers (ECNF)) were additionally oxidized in air at 800°C under reduced pressure (electrospun carbon nanofibers oxidized under reduced pressure (ECNFV)) . The oxidative treatment led to partial removal of a structurally less-ordered carbon phase from the near-surface region of the carbon nanofibers. Both types of carbon fibrous mats were studied using scanning electron microscopy (SEM), high-resolution transmission electron microscopy (TEM), XRD, and Raman spectroscopy. The morphology, microstructure, and surface properties of both materials were analyzed. The oxidative treatment of carbon nanofibers significantly changed their surface morphology and physical properties (wettability, surface electrical resistance). Biological tests (genotoxicity, fibroblast, and human osteoblast-like MG63 cultures) were carried out in contact with both materials. Genotoxicity study conducted by means of comet assays revealed significant differences between both carbon nanofibers. Fibroblasts contacted with the as-received carbon nanofibers (ECNF) showed a significantly higher level of DNA damage compared to control and oxidized carbon nanofibers (ECNFV). The ECNFV nanofibers were not cytotoxic, whereas ECNF nanofibers contacted with both types of cells indicated a cytotoxic effect. The ECNFV introduced into cell culture did not affect the repair processes in the cells contacting them.